2017
DOI: 10.2174/1389450117666160208145432
|View full text |Cite
|
Sign up to set email alerts
|

Virological and Clinical Response to Interferon-Free Regimens in Patients with HCV-Related Mixed Cryoglobulinemia: Preliminary Results of a Prospective Pilot Study

Abstract: Mixed Cryoglobulinemia (MC) is the most frequent extrahepatic manifestation of Hepatitis C virus (HCV) infection. MC is an autoimmune /B-cell lymphoproliferative disorder characterized by circulating immune-complexes, named cryoglobulins. MC patients exhibit symptoms due to a systemic vasculitis of small/medium size vessels (mixed cryoglobulinemia syndrome, MCS) in a percentage going from 5 to 30%. The first-line therapeutic option in MCS patients is the etiologic treatment and, in the past fifteen years, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 0 publications
6
53
0
Order By: Relevance
“…50 Data on the use of DAAs in mixed cryoglobulinemia are emerging with encouraging results. [51][52][53][54] Rituximab was shown to be effective in HCV-associated cryoglobulinemia. In a prospective cohort study, the addition of rituximab to pegylated interferon-ribavirin resulted in a shorter time to response and better renal response and cryoglobulin clearance, although the rate and depth of clinical response and the relapse rate were similar between study arms.…”
Section: Case 4: Hcv-associated (Infectious) Mixed Cryoglobulinemiamentioning
confidence: 99%
“…50 Data on the use of DAAs in mixed cryoglobulinemia are emerging with encouraging results. [51][52][53][54] Rituximab was shown to be effective in HCV-associated cryoglobulinemia. In a prospective cohort study, the addition of rituximab to pegylated interferon-ribavirin resulted in a shorter time to response and better renal response and cryoglobulin clearance, although the rate and depth of clinical response and the relapse rate were similar between study arms.…”
Section: Case 4: Hcv-associated (Infectious) Mixed Cryoglobulinemiamentioning
confidence: 99%
“…Recently it has been shown that HCV infection may lead to a substantial reduction in quality of life, with a key role played by depression, cognitive disorders and asthenia (60). The correct diagnosis of HCVrelated EHMs is clinically important to ensure early detection of the infection and prevent evolution towards LPD and NHL, starting the best treatment that in the majority of subjects should A c c e p t e d M a n u s c r i p t 18 be antiviral therapy with DAAs, despite no significant liver damage (61)(62)(63)(64). It should be emphasized that antiviral therapy for HCV was clearly shown to be effective against a wide spectrum of EHMs.…”
Section: Extra-hepatic Manifestationsmentioning
confidence: 99%
“…So far, a few studies have reported promising results on the efficacy and tolerability of DAA therapy in patients with HCV‐associated MC, either in association with IFN or using IFN‐free regimens, and in patients with HCV‐associated NHL …”
mentioning
confidence: 99%